2016
DOI: 10.1177/2045125316674698
|View full text |Cite
|
Sign up to set email alerts
|

Does the efficacy of asenapine in bipolar disorder increase in the presence of comorbidity with a substance use disorder? A naturalistic study

Abstract: Background: Asenapine is a second-generation antipsychotic approved in Europe for treating moderate-to-severe manic episodes in adults affected by type I bipolar disorder (BD-I). We aimed to compare its efficacy in psychiatric inpatients with BD-I, with or without substance use disorder (SUD). Methods: We administered flexible asenapine doses ranging from 5-20 mg/day to 119 voluntarily hospitalized patients with Diagnostic and Statistical Manual of Mental Disorders, 4th Edition, Text Revision (DSM-IV-TR) BD-I … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The inclusion criteria were as follows: (1) GAD was diagnosed according to the diagnostic criteria from the American Diagnostic and Statistical Manual of Mental Disorders , 5th ed. [ 29 ]; (2) patients complained of uncontrollable anxiety and worries about everyday events and problems for at least 6 months; (3) patients were 20–40 years old; (4) all the participants were right-handed; and (5) GAD patients had the HAMA score higher than 14.…”
Section: Methodsmentioning
confidence: 99%
“…The inclusion criteria were as follows: (1) GAD was diagnosed according to the diagnostic criteria from the American Diagnostic and Statistical Manual of Mental Disorders , 5th ed. [ 29 ]; (2) patients complained of uncontrollable anxiety and worries about everyday events and problems for at least 6 months; (3) patients were 20–40 years old; (4) all the participants were right-handed; and (5) GAD patients had the HAMA score higher than 14.…”
Section: Methodsmentioning
confidence: 99%
“…Nonetheless, their pharmacokinetics, pharmacodynamics, and ADRs regarding BD have wide-ranging variations [94]. It has been reported that quetiapine, asenapine, and lurasidone show better preventive potential towards depressive episodes of BD [95][96][97][98][99]. Additionally, antipsychotics are the rational alternative for patients with BD who are oversensitive or have poor compliance to Li therapy for relapse prevention (Figure 5) [99,100].…”
Section: Lithium Vs Antipsychotics/anticonvulsants In Bipolar Disordermentioning
confidence: 99%
“…These patients were not included in final analysis. The inclusion criteria were as follows: (I) the patients were diagnosed with GAD according to the diagnostic criteria from the American Diagnostic and Statistical Manual of Mental Disorders (5th ed) (25) and not treated before admission; (II) patients complained of uncontrollable anxiety and worried about everyday events and problems for at least 6 months; (III) patients were 20-40 years old; (IV) all the participants were right-handed; (V) GAD patients had the HAMA score higher than 14, but lower than 29 (HAMA score <21, mild; 29> HAMA score ≥21: moderate), the Hamilton Depression Scale (HAMD) score (17 items) was <7; (VI) patients were not diagnosed with mental retardation and had no history of head injury or neurological trauma that resulted in a loss of consciousness (26). The study protocol was approved by the Ethics Committee of Dongzhimen Hospital of Tongzhou District, Beijing University of Chinese Medicine Medical (NO.…”
Section: Participantsmentioning
confidence: 99%